The mediating role of social identity complexity on intergroup attitudes - Tan, Kendis Wen Ting (Nanyang Technological University, 2023)
As social media platforms become increasingly popular in raising awareness of everyday racism by sharing personal experiences of discrimination, it is imperative to further explore the effects of intergroup contact facilitated through these platforms. The present study seeks to investigate the impact of vicarious mediated intergroup contact on outgroup attitude in a moderated mediation model, with social identity complexity as the mediator and multiple ingroup identity salience as the moderator. Social identity complexity is defined as the overlap and similarity between social identities. Our hypothesis posits an overall positive indirect effect of vicarious mediated intergroup contact on outgroup attitudes via social identity complexity, moderated by multiple ingroup identity salience, such that the indirect effect is stronger for participants in the increased salience condition compared to those in the maintained salience condition. Our sample comprised 456 Chinese Singaporeans (228 female, 2 undisclosed, Mage = 42.91, SDage = 11.95) recruited through an online survey panel. Prior to and after undergoing a salience manipulation (maintained or increased salience) and vicarious mediated intergroup contact, we measured the participants’ ingroup and outgroup attitudes, as well as social identity complexity, among other variables. Our analyses revealed a significant negative indirect effect of vicarious mediated intergroup contact on outgroup attitudes via overlap complexity for participants in the increased salience condition. We discuss the potential explanations for these unexpected findings and highlight the unintended negative consequences that may arise from promoting vicarious mediated intergroup contact on social media.